2009
DOI: 10.1111/j.1651-2227.2009.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting health‐related quality of life of parents of children with inherited metabolic diseases

Abstract: Psychosocial determinants appeared more important in predicting parental HRQoL than medical and socio-demographic variables. Interventions should be focused on supporting parents combining the care for their children with a social life. Further research on this subject is necessary. In the meantime, involved medical specialists should pay structural attention to parental functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
34
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 21 publications
11
34
0
4
Order By: Relevance
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research in this area has identified parents’ use of a range of strategies that included proactive coping, other positive coping strategies (e.g., religion, emotional/social support), and less adaptive means of coping (such as substance use) [24]. Similar to our study, others have identified social support, including close family and friend relationships [5, 20, 25, 26] and social media [27], as important to caregiver and family well-being. These informal support systems were commonly identified as important in our study, while the receipt of formal psychological or counselling services was mentioned less frequently by participants.…”
Section: Discussionsupporting
confidence: 78%
“…However, in conditions like PKU, the caring of a child on a special diet does not appear to affect the quality of life of the parents. However, factors such as loss of carer friendships and lack of emotional support have a large negative impact [20,21]. …”
Section: The Paradox Of Dietary Managementmentioning
confidence: 99%
“…Furthermore, there is a close relation between the parent’s rating of a child’s HrQoL and the parent’s own HrQoL [32]: Parents experiencing low HrQoL rate their child’s HrQoL low as well. This might be especially relevant in parents of children with IT-IEM, since these diseases demand intensive care and may have a great impact on the lives of caregivers [33]. Another explanation for the lower proxy-ratings may be the ability of parents to anticipate the future problems of the child.…”
Section: Discussionmentioning
confidence: 99%